GENDER STEREOTYPES AND ITS PSYCOLOGICAL IMPACT PORTRAYED IN MULAN 1998 MOVIE - Diyah Fitri Wulandari; Afresti Fahiratunnisa (Universitas Duta Bangsa Surakarta, 2024)
Gender stereotypes are beliefs about individuals’ traits and behaviors based on gender. These preconceptions of gender stereotypes influenced society and shaped individual beliefs, attitudes, and experiences. This study examines the psychological impact of gender stereotypes towards Mulan as reflected in the Mulan (1998) movie. More specifically, this study aims to determine the psychological impact of negative stereotypes on women that are embedded in the beliefs of a patriarchal society. This research applies Erik Erikson’s developmental psychology theory to examine the psychological impact of gender stereotypes on Mulan as an adolescent girl. This study analyzed the data consisting of words, sentences, and dialogues using a qualitative approach. The data was collected through several steps, such as watching and reading the movie script, identifying, and classifying. Based on the findings of this study, Mulan’s psychological development is impacted by gender stereotypes in several aspects, including low self-esteem, future career, and social roles.